SYAHRUR, POLYGAMY, AND CHILD PROTECTION IN INDONESIA - Dede Nurohman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research examines Syahrur's thoughts on polygamy through his theory and methodology. The concept is connected or sought for its relevance to child protection efforts in Indonesia as reflected in the Child Protection Law No. 23 of 2002. This research is a library in nature, which operationally processes the substance of texts related to the formulation of research problems theoretically and analytically. The approach used is the character approach i.e., the exploration of Muhammad Syahrur's thoughts and theoretical framework. The results of this study reveal that according to Syahrur polygamy can be done as long as it meets several criteria, (1) the number of wives that can be married is 4 with the provision that the first wife may be a virgin or widow who has orphans or not. While the second, third and or fourth wives must be widows who have children. (2) must be able to create fair conditions, either for his wives or his children. This conception has relevance to the child protection law, which is reflected in the following; First, Syahrur's attention to the lives of orphans is part of the Indonesian government's goal of protecting all children in general. Secondly, the importance of family integrity where the mother and father are in it to work together to pay attention to the lives of their children. However, at this point, Syahrur suggests that the child's mother find a foster father by means of polygamy, while the Indonesian government directs her to find an adoptive father or foster father, (3) Syahrur's concept of polygamy can provide a new discourse on the concept of polygamy in Indonesia by linking the Marriage Law 1 of 1974 and Government Regulation No. 10 of 1983 articles 55-59 KH. 10 of 1983 articles 55-59 KHI with the Child Protection Law No. 23 of 2002 which proclaims the need for child protection, and (4) Syahrur's polygamy requirements are in line with the principles of child protection in Indonesia i.e., nondiscrimination, the best interests of the child, the right to life, survival and development, and respect for the child's opinion.